Palaeobiogeographical significance of Early Silurian thelodonts from central Asia and southern Siberia - Zigaite, Zivile; Blieck, Alain (HAL CCSD, 2006)
Early Silurian vertebrates, especially agnathans, from central Asia (Tuva and norhwestern Mongolia) and southerrn Siberia are abundant and diverse. The numerous microremains indicate that the strata of this region were deposited in warm, productive, shallow marine basins. The thelodont microremains concerned with in this paper are assigned to three genera, viz., Longanellia Turner, 1991, Angaralepis Karatajte-Talimaa, 1997, and Talimaalepis Zigaite, 2004, of which the latter two are endemic to the region. In central Tuva, L. tuvaensis Karatajte-Talimaa, 1978 is restricted to the Lower Silurian. This species is, however, considered to occur also in the Upper Silurian-Lower Devonian of north Greenland. Taking into account the taxonomic record of early thelodonts, central Asia and southern Siberia may be considered as a centre of origin and radiation of silurian thelodonts. It may have corresponded to a palaeobiogeographical province.